2023
DOI: 10.1111/febs.16820
|View full text |Cite
|
Sign up to set email alerts
|

The role of lysosomal membrane proteins in autophagy and related diseases

Abstract: As a self‐degrading and highly conserved survival mechanism, autophagy plays an important role in maintaining cell survival and recycling. The discovery of autophagy‐related (ATG) genes has revolutionized our understanding of autophagy. Lysosomal membrane proteins (LMPs) are important executors of lysosomal function, and increasing evidence has demonstrated their role in the induction and regulation of autophagy. In addition, the functional dysregulation of the process mediated by LMPs at all stages of autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 181 publications
0
0
0
Order By: Relevance
“…In agreement with this observation, the study by Kornhuber and colleagues showed that lysosomal pH is not changed by amitriptyline [95]. Nevertheless, the accumulation of amitriptyline into the lysosomal lumen, as lysosomotropic drug, may affect lysosomal membrane permeability [95] and lysosomal enzymes activity accounting for the delay of autophagic cargo degradation [96,97].…”
Section: Discussionmentioning
confidence: 65%
“…In agreement with this observation, the study by Kornhuber and colleagues showed that lysosomal pH is not changed by amitriptyline [95]. Nevertheless, the accumulation of amitriptyline into the lysosomal lumen, as lysosomotropic drug, may affect lysosomal membrane permeability [95] and lysosomal enzymes activity accounting for the delay of autophagic cargo degradation [96,97].…”
Section: Discussionmentioning
confidence: 65%
“…Where PTC transcripts persist, our data are more consistent with ribosomal readthrough and incorporation of missense substitutions tolerated to differing degrees, than generation of peptides truncated at the PTC. In patient cells, where aberrant protein expression would be low, governed not only by low level RNA transcripts but also by usually rapid endoplasmic reticulum–associated degradation (ERAD) 96 and/or lysosomal 97 degradation, further studies will be required to establish whether and when levels are negligible or not negligible, and whether this differs between missense variants for which cellular processes can adapt to chronic proteotoxic loads, 98 , 99 and PTC variants for which levels are more fluctuant.…”
Section: Discussionmentioning
confidence: 99%